Financial Sector Ups and Downs and the Real Sector : Big Hindrance, Little Help - Aizenman, Joshua; Pinto, Brian; Sushko, Vladyslav (2012)
This paper examines how financial expansion and contraction cycles affect the broader economy through their impact on eight real economic sectors in a panel of 28 countries over 1960-2005, paying particular attention to large, or sharp, contractions and magnifying and mitigating factors. Overall, the construction sector is the most responsive to financial sector growth, with a number of others -- such as government, public utilities, and transportation -- also exhibiting significant sensitivity to lagged financial sector growth. Sharp fluctuations in the financial sector have asymmetric effects, with the majority of real sectors adversely affected by contractions but not helped by expansions. The adverse effects of financial contractions are transmitted almost exclusively by the financial openness channel with foreign reserves mitigating these effects with a sizeable (10 to 15 times greater) impact during sharp financial contractions. Both effects are magnified during particularly large financial contractions (with coefficients on interaction terms two to three times greater than when all contractions are considered). Consequent upon a financial contraction, the most severe real sector contractions occur in countries with high financial openness; relative predominance of construction, manufacturing, and wholesale and retail sectors; and low international reserves. Finally, the analysis finds that abrupt financial contractions are more likely to follow periods of accelerated growth, indicative of "up by the stairs, down by the elevator dynamics."